COPYWRITING PATTERNS IN ARTICLES OF TRADITIONAL ISLAMIC BOARDING SCHOOL WEBSITES IN INDONESIA - Dwi Harmoko, Danang; Dewanti, Ratna; Mayuni, Ilza (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study investigates the structure of persuasive religious discourse in articles published on the websites of salafi or traditional pesantren in Indonesia. These texts, while primarily expository, increasingly experiment with elements of digital copywriting. The study applies Victor Schwab’s five-point copywriting formula Get Attention, Show an Advantage, Prove It, Persuade, and Ask for Action as an analytical framework, combined with Moustakas’ social phenomenology to explore the intentionality behind language use. A corpus of 30 articles from five pesantren websites was examined using linguistic-textual analysis focusing on transitivity, modality, theme-rheme structures, and lexical salience. The findings reveal that although traces of Schwab’s persuasive stages are present, their distribution is inconsistent: less than three-quarters of the articles apply the “Get Attention” stage effectively, and fewer than half conclude with a clear “Ask for Action.” Similarly, the stages of “Show an Advantage” and “Prove It” appear only in about half of the dataset, indicating a fragmented adaptation of persuasive techniques. These results suggest that pesantren articles tend to blend theological exposition with partial persuasive strategies, rather than consistently following an established copywriting sequence. This study thus highlights the need for further research to conceptualize a model of Islamic copywriting that reflects the rhetorical particularities of pesantren discourse. By foregrounding both the presence and the gaps in persuasive structures, this research contributes to applied linguistics and Islamic studies by showing that the digital rhetoric of salafi pesantren remains in transition: adopting elements of marketing logic while still anchored in traditional modes of religious instruction.